Aquatic Food Systems and Stunting: A Structured Literature Review of Policy Interventions for SDG 2 (Zero Hunger) and SDG 3 (Good Health and Well-being) - Sehbayang , Nico; Arshad , Imran (CV. Bimbingan Belajar Assyfa, 2025)
Aquatic food systems hold significant potential in addressing the global challenge of stunting, particularly in the context of achieving Sustainable Development Goals 2 (Zero Hunger) and 3 (Good Health and Well-being). The growing recognition of the importance of these systems in global nutrition has prompted this structured literature review, which examines policy interventions from 2022 to 2025. The primary objective of this research is to evaluate the effectiveness of various policies related to fish production, distribution, and consumption in reducing stunting. Employing a comprehensive review methodology, this study synthesizes data from multiple sources to identify successful strategies and best practices. The findings reveal that policies integrating aquaculture development, nutrition education, and social protection measures yield the most substantial reductions in stunting rates. Such integrated approaches are crucial for enhancing nutritional outcomes and supporting the attainment of SDG 2 and SDG 3. The study concludes that cross-sectoral collaboration is essential to amplify the impact of these interventions.